New Possibilities for Evaluating Markers of Alzheimer's Disease in Blood Serum - S. V. Vorobev; A. Yu. Plekhanov; I. K. Ternovykh; A. S. Usikov; A. А. Lebedev; A. N. Smirnov; N. M. Shmidt; M. S. Dunaevskiy; S. P. Lebedev (Антибиотики и Химиотерапия)
Given the steady increase in the number of cases of Alzheimer's disease, the issue of improving the level of its diagnosis is becoming more urgent.   The aim of the study was to develop a new method for verifying markers of Alzheimer's disease in blood serum based on graphene sensors.   Materials and methods. Graphene growth was carried out by sublimation. At the first stage of the experiment, the effectiveness of antibody attachment to human beta-amyloid peptide 1–42 and human total tau protein was evaluated. At the second stage, the sensors' ability to analyze beta-amyloid 1–42 proteins and total tau protein was evaluated.   Results. Graphene functionalized with sulfo groups from pyranine exhibits sufficient ability to immobilize antibodies. Treatment with glutaraldehyde of graphene functionalized by amino groups significantly increases the ability of the latter to immobilize antibodies. The sensors exhibit high sensitivity at protein concentrations in solutions from 10–10 to 10–15 g/ml. At low concentrations of antigen, the obtained calibration graphs steeply drop and slightly diverge, which makes it possible to use this area to determine an unknown concentration of antigen. The concentration of proteins in the blind experiment was determined with an error of 1.5 times, that is, about half the dilution step. A more fractional dilution of samples will help to achieve greater accuracy, which shows the fundamental applicability of the approach used.   Conclusion. The research conducted to date has allowed the development of medical, as well as physicochemical aspects of the action of graphene-based sensors for detecting low concentrations of beta-amyloid and tau protein proteins in media. The fundamental technical efficiency of this technique has been demonstrated.